Global research landscape and trends of lung cancer immunotherapy: A bibliometric analysis - Liu, Yanhao; Cheng, Xu; Han, Xiaona; Cheng, Xi; Jiang, Shu; Lin, Yaru; Zhang, Zhen; Lu, Linlin; Qu, Baozhen; Chen, Yuxian; Zhang, Xiaotao (Frontiers in Immunology, 2022)
Background: Immunotherapy for lung cancer has been a hot research area for years. This bibliometric analysis aims to present the research trends on lung cancer immunotherapy. Method: On 1 July, 2022, the authors identified 2,941 papers on lung cancer immunotherapy by the Web of Science and extracted their general information and the total number of citations. A bibliometric analysis was carried out to present the research landscape, demonstrate the research trends, and determine the most cited papers (top papers) as well as major journals on lung cancer immunotherapy. After that, recent research hotspots were analyzed based on the latest publications in major journals. Results: These 2,941 papers were cited a total of 122,467 times. “Nivolumab vs. docetaxel in advanced non–squamous non–small–cell lung cancer” published in 2015 by Borghaei H et al was the most cited paper (5,854 citations). Among the journals, New England Journal of Medicine was most influential. Corresponding authors represented China took part in most articles (904) and papers with corresponding authors from the USA were most cited (139.46 citations per paper). Since 2015, anti–PD–(L)1 has become the hottest research area. Conclusions: This bibliometric analysis comprehensively and quantitatively presents the research trends and hotspots based on thousands of publications, and further suggests future research directions. Moreover, the results can benefit researchers to select journals and find potential collaborators. This study can help researchers get a comprehensive impression of the research landscape, historical development, and recent hotspots in lung cancer immunotherapy and provide inspiration for further research.